Being prepared for natural disaster - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Agricultural rehabilitation needs to be a part of disaster response planning, including preservation and supply of local planting materials.